Intermuscular coordination during pendulum rebound exercises - Rodacki, A. L; Fowler, N. E. (Journal of Sports Sciences, 2001)
In this study, we assessed coordination during pendulum rebound jumps. To gain insight into the movement coordination strategy, nine experienced male volleyball players performed maximal rebound jumps in a pendulum swing device using three different seat arrangements (90 degrees, 135 degrees and 180 degrees). Two-dimensional filming was performed in the right sagittal plane (200 Hz) synchronized with a force platform fitted to the wall (1000 Hz). The surface electromyograms of five muscles were recorded (200 Hz), in conjunction with kinematic and kinetic assessment. During the countermovement phase, the impact forces were attenuated by eccentric contractions of most muscles, which helped to reduce the energy input into the system. The wall reaction forces, net moments and joint power profiles were comparable between conditions. The small differences found between the extreme seat arrangements were attributed to differences in muscle length and the position of the feet. The strategy used during landing was similar to that observed in unconstrained vertical and drop jumps, where the neuromuscular system attenuates the impact forces. During the push-off phase, most muscles were found to contribute to positive work generation, except the semitendinosus, which was stretching throughout the propulsive phase. Despite not being able to exert a large influence over the trunk segment, this muscle was deemed to play an important role in regulating and synchronizing the onset of knee extension, enabling hip extension to occur before extension in the other more distal joints. Our findings show that the neuromuscular system is able to produce consistent movement coordination across experimental conditions and in accordance with the specific task demands and constraints imposed in the movement structure.